STOCK MARKET INVESTORS MECHANICS AND THEIR BLUNDERS - Kumar, Ravi; Sajjan, Rohini (International Journal of Research -GRANTHAALAYAH, 2016)
Investment mistakes happen for a multitude of reasons, including the fact that decisions made under conditions of uncertainty that are irresponsibly downplayed by market gurus and institutional spokespersons. Losing money on an investment may not be the result of a mistake, and not all mistakes result in monetary losses. But errors occur when judgment is unduly influenced by emotions, when the basic principles of investing are misunderstood, and when misconceptions exist about how securities react to varying economic, political, and hysterical circumstances. Proper planning and using of techniques, strategies can come as rescue to the investor and help in reaping profits and avoiding the blunders that are commonly observed. The paper investigates the basis for investment patter by the investor, their techniques and strategies adopted and guidelines to be followed to avoid the common blunders made by them leading to fewer losses they would face otherwise.